PROTECTIONISM OR PROTECTION? NEW WESTERN ECONOMIC POLICIES AGAINST THE BACKDROP OF THE CURRENT GEOECONOMIC SCENARIO - Pompeo Della Posta (PEOPLE: International Journal of Social Sciences, 2025)
In this article I discuss the current situation in which many Western countries are reconsidering the supply chain and free trade policies they embraced until not so long ago, when leadership in technologically advanced products was firmly in their hands. This paradigm shift is claimed to be dictated by the need to protect Western economies from the potential threat from China in particular, rather than adopting protectionist policies with the simple (and understandable) motivation of shielding domestic producers from foreign competitors. This means that the change in the policies of Western countries is not the result of a revision of the theoretical principles that have guided their economic policies in the past, as these principles are believed to retain their full validity. Instead, the revision would be induced by an exception that has always been admitted by orthodox economic theory, namely protection from a military and external security threat. My main claim is that the need to adopt what can unequivocally be called standard protectionist policies, instead, should stem from a serious revision of the previously adopted theoretical paradigm, given the many negative outcomes derived from its blind application. Moreover, justifying the adoption of overtly protectionist policies with the need for protection, something that is far from proved, risks triggering a negative self-fulfilling process, thereby fuelling a dangerous confrontation between separate blocs, something which does not promise anything good for our future.